2017
DOI: 10.3389/fendo.2017.00220
|View full text |Cite|
|
Sign up to set email alerts
|

Dose-Dependent and Lasting Influences of Intranasal Vasopressin on Face Processing in Men

Abstract: Arginine vasopressin (AVP) and related peptides have diverse effects on social behaviors in vertebrates, sometimes promoting affiliative interactions and sometimes aggressive or antisocial responses. The type of influence, in at least some species, depends on social contexts, including the sex of the individuals in the interaction and/or on the levels of peptide within brain circuits that control the behaviors. To determine if AVP promotes different responses to same- and other-sex faces in men, and if those e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Price et al [49] conducted a study to determine if AVP promotes different responses to same- and other-sex faces in men, and if those effects are dose-dependent. The investigators included 86 male subjects between the ages of 18 and 30 years.…”
Section: Resultsmentioning
confidence: 99%
“…Price et al [49] conducted a study to determine if AVP promotes different responses to same- and other-sex faces in men, and if those effects are dose-dependent. The investigators included 86 male subjects between the ages of 18 and 30 years.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison experiments between intranasal administration and peripheral injection are necessary to distinguish AVP targets more clearly. Furthermore, dosage may impact the effect of AVP; a recent study reported that when 20 IU was administered intranasally, male participants gave more negative subjective ratings to same- or other-sex faces, relative to placebo and 40 IU 37 . While we used 40 IU here following the protocol of a recent game experiment 17 , systematic manipulation of dosage may shed light on boundary conditions of the agonistic or affiliative effects of AVP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using different amounts of oxytocin are needed to examine possible threshold differences among individuals as a function of sex, experience, and emotional lability (Goldman et al, 2011). Different doses of a given peptide can produce different effects (Ceanga et al, 2010;Klein et al, 2014;Borland et al, 2019), and dose-response curves are only just appearing in the in vivo literature (Price et al, 2017).…”
Section: Pharmacology and Oxytocin: Issues In Therapeutic Applicmentioning
confidence: 99%